ADMINISTRATIVE INFORMATION SYSTEMS COMPUTERIZED OWNED HOUSE AT UNIT PERUMAS PERUM KARAWACI - Fx. Chrisbijantoro; Ir. Aqwam Rosadi Kardian (Jurnal Sistem Informasi, 1996)
In order to improve utilization of the management of Home Ownership InformationSystems Administration Unit at Perumnas Karawaci, so needed a good data handlingsystems and can provide information quickly. Efforts to address those needs is to usecomputer tools, because the computer can process large amounts of data with highspeed and accuracy. The speed of presenting the information will greatly assist theleadership in policy-making steps and decisions that impact will be able to advancethe Company.